PHYSICAL AND SOCIAL VULNERABILITY IN THE HOUSHOLD LEVEL TOWARDS TSUNAMI IN SADENG COASTAL AREA, GUNUNGKIDUL - Fitria Nucifera; Sutanto Trijuni Putro; Sakinatul Afidah (JURNAL GEOGRAFI, 2021)
Tsunami occurrence in Indonesia has continued to increase until 2018. The southern coast of Java is one of the tsunami-prone areas because it is located in a subduction zone. Study location is Sadeng coastal area which is located in the south coast of DIY Province. Disaster vulnerability studies at the household level is still limited, so this paper aims to identify physical and social vulnerability to tsunami hazard at the household level. The data of this research was obtained by invterviewing household respondents and observing physical condition of building. Identification of physical vulnerability was performed using modified SCHEMA and PTVA-3 method, while social vulnerability assessment considered demographic and socio-economic parameters. Total vulnerability was retrieved from matrix analysis of physical and social vulnerability classification. The study shows that 64 % households in Sadeng coastal areas are classified to moderate vulnerability, 30% of households are high vulnerability and 6 % of households are low vulnerability.  High vulnerability is characterized by households which occupy non-permanent houses, have no economic assets, and have a high dependency ratio. Moderate vulnerability is characterized by households which occupy semi-permanent house, have economic assets, but have high dependency ratio. Low vulnerability is characterized by households which live in government-owned buildings, have economic assets, and have low dependency ratio. Keywords: tsunami, vulnerability, building`s physical vulnerability, social vulnerabilityKejadian tsunami di Indonesia terus mengalami peningkatan hingga tahun 2018. Pesisir selatan Jawa merupakan salah satu kawasan yang terpapar bahaya tsunami karena terletak pada zona subduksi. Lokasi kajian adalah kawasan pesisir Sadeng yang berlokasi di pesisir selatan Propinsi DIY. Kajian kerentanan bencana di tingkat rumah tangga belum banyak dilakukan, sehingga tulisan ini bertujuan untuk melakukan identifikasi kerentanan fisik bangunan dan sosial terhadap bencana tsunami di tingkat rumah tangga. Perolehan data penelitian dilakukan dengan wawancara responden rumahtangga dan observasi kondisi fisik bangunan. Identifikasi kerentanan fisik bangunan dilakukan dengan metode SCHEMA dan PTVA-3 yang dimodifikasi, sedangkan penilaian kerentanan sosial mempertimbangkan parameter kependudukan dan sosial ekonomi. Nilai total kerentanan diperoleh dari analisis matriks klasifikasi kerentanan sosial dan fisik bangunan. Kajian menunjukkan bahwa sebesar 64 % rumahtangga di kawasan pesisir Sadeng termasuk dalam kelas kerentanan sedang, 30 % rumahtangga dalam kerentanan tinggi dan 6 % rumahtangga dalam kerentanan rendah. Tingkat kerentanan tinggi dicirikan dengan rumahtangga yang menempati rumah tinggal non-permanen, tidak memiliki asset ekonomi, dan memiliki angka ketergantungan yang tinggi. Tingkat kerentanan sedang dicirikan dengan rumahtangga yang menempati rumah tinggal semi permanen, memiliki asset ekonomi namun memiliki angka ketergantungan yang tinggi. Tingkat kerentanan rendah dicirikan dengan rumahtangga yang tinggal pada bangunan milik pemerintah, memiliki asset ekonomi, dan memiliki angka ketergantungan yang rendah.  Kata kunci: tsunami, kerentanan, kerentanan fisik bangunan, kerentanan sosial